Code-Switching and Code-Mixing Found in a Youtube Channel Called Nessie Judge - Nona Ruth Anjely Hutapea (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study deals with code-switching and code-mixing found in Nessie Judge YouTube channel. Code switching is about the language that switched from their native language to the other language while they are in the conversation. Code mixing is about the language that mixes in variations because they had competence in the language. The objective of this thesis to find the types of code switching and code mixing used by Nessie Judge YouTube channel when she conveying the story using the English language and Indonesia language. In order to conduct the research, the writer used the qualitative research approach. The data is taken from language of the character in which it contains two languages. It is found that the types of Code-Switching used by Nessie Judge on her YouTube Channel are intra-sentential code-switching,inter-sentential code-switching, and tag switching. From the data, the writer found 19 intra-sentential code-switching, 21 inter-sentential code-switching, and 6 tag-switching by replacing a single word or phrase. Second, it found that the types of code mixing used by Nessie Judge in the YouTube channel are insertion, alternation, and congruent lexicalization. From the data, the writer found 21 insertions, 17 alternations, and 12 congruent lexicalizations.